2009
DOI: 10.4028/www.scientific.net/kem.409.354
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Thermophysical and Tribological Properties of CNT Reinforced Si<sub>3</sub>N<sub>4</sub>

Abstract: Thermophysical and tribological measurements have been performed on carbon nanotube added silicon nitride composites. Higher thermal conductivity values were observed in the case of the sample with CNT than for the reference sample. As was observed from tribological measurements, nanocomposite Si3N4 without carbon nanotubes shows a higher friction coefficient than carbon nanotube - Si3N4. The results of wear study indicate that the Si3N4 ball (used as static partner) was more damaged with MWCNTs addition nanoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 21 publications
(17 reference statements)
0
12
0
Order By: Relevance
“…In these composites, the addition of CNTs usually led to the reduction of friction and wear rate compared with monolithic Al 2 O 3 , but results were greatly dependent on the presence of CNTs agglomerates 8,9 . Just one work reports about the tribological properties of Si 3 N 4 /CNTs composites at low loads obtained by dry ball‐on‐plate tests 12 . Results showed a slight decrease in friction for composites containing 3 wt% of CNTs, whereas the wear rate increased one order of magnitude due to the presence of CNTs agglomerates.…”
Section: Introductionmentioning
confidence: 99%
“…In these composites, the addition of CNTs usually led to the reduction of friction and wear rate compared with monolithic Al 2 O 3 , but results were greatly dependent on the presence of CNTs agglomerates 8,9 . Just one work reports about the tribological properties of Si 3 N 4 /CNTs composites at low loads obtained by dry ball‐on‐plate tests 12 . Results showed a slight decrease in friction for composites containing 3 wt% of CNTs, whereas the wear rate increased one order of magnitude due to the presence of CNTs agglomerates.…”
Section: Introductionmentioning
confidence: 99%
“…According to Miranzo et al [97], β phase content has a positive effect in enhancing the thermal conductivity. To our understanding, the enhancement of thermal conductivity of the composite claimed by Koszor et al [91] was likely due to the presence of β phase, not of the CNTs.…”
Section: Thermal Conductivitymentioning
confidence: 63%
“…Figures 12 and 13 illustrate the influence of CNT addition on wear rate and the coefficient of friction during the tribological tests of CNT-reinforced silicon nitrides tested up to now. Koszor et al reported that the friction coefficient decreased with the addition of 3 wt.% MWCNTs in Si 3 N 4 composite [91]. The wear rate of monolithic silicon nitride composite was reported to be 3.02 × 10 −6 mm 3 /N•m and the addition of 3 wt.% MWCNTs reduced the wear to 3.34 × 10 −5 mm 3 /N•m [91].…”
Section: Tribological Propertiesmentioning
confidence: 99%
See 2 more Smart Citations